God in politics : Islamism and democracy in Bangladesh - Islam, Md Nazrul (2017)
Religion remains a dominant social institution and a topic of sociological inquiry. This research has explored the complex interplay among Islam, Islamism and democracy in Bangladesh, addressing some pressing questions: What is the relationship between Islamic tradition and democracy? What is the origin and development of Islamic tradition in Bangladesh? What are the key social and historical trajectories through which Islamism has developed in Bangladesh, and what specific roles, if any, did state and non-state actors play in that promotion? Who are the Islamists and what is their role in the politics of Bangladesh? How is secularism understood and practiced in Bangladesh? How do the Bangladeshi Islamists see secularism and democracy? Drawing on the theories of secularism and Weberian sociology of religion (along with conceptual threads such as polyarchy and hybridity of democracy), this study addresses these research questions. A triangulation of methods comprised of in-depth interviews, content analysis, and focus group discussions has been employed in this research. The study has found that Islam and democracy are not necessarily incompatible. Islam was spread in Bangladesh largely through peaceful missionary activities with both state and non-state actors making contributions to Islamism through Islamization in Bangladesh. While the Islamic parties in general are characterized by factionalism, disintegration and dynastic politics, the mainstream Islamic parties have little or no tension with democracy in Bangladesh. Secularism was imposed, not established based on the consensus of the people, and both militant Islamism and militant secularism are equally fundamentalist in nature and contradictory to the sociopolitical and cultural landscape of Bangladesh.